IDNLearn.com is committed to providing high-quality answers to your questions. Get step-by-step guidance for all your technical questions from our knowledgeable community members.
Sagot :
To solve the given equation for [tex]\(h\)[/tex], we will isolate [tex]\(h\)[/tex] on one side of the equation. Here are the steps:
1. Start with the given equation:
[tex]\[ (5 - 3)p = 4h + 2p \][/tex]
2. Simplify the left-hand side first:
[tex]\[ 2p = 4h + 2p \][/tex]
3. Next, we need to isolate [tex]\(h\)[/tex]. To do that, we subtract [tex]\(2p\)[/tex] from both sides of the equation:
[tex]\[ 2p - 2p = 4h + 2p - 2p \][/tex]
4. This simplifies to:
[tex]\[ 0 = 4h \][/tex]
5. Now, divide both sides by 4 to solve for [tex]\(h\)[/tex]:
[tex]\[ \frac{0}{4} = \frac{4h}{4} \][/tex]
6. Simplifying this gives:
[tex]\[ 0 = h \][/tex]
So, the solution for [tex]\(h\)[/tex] is:
[tex]\[ h = 0 \][/tex]
This shows that [tex]\(h\)[/tex] must be zero to satisfy the original equation. Additionally, the simplified form of the initial equation:
If we write the equation in a standard linear form related to [tex]\(h\)[/tex]:
[tex]\[0 = -4h\][/tex]
Here, the expression simplifies to:
[tex]\[ -4h \][/tex]
Therefore, the complete solution shows that:
The simplified version of the equation is [tex]\(-4h = 0\)[/tex], and the solution for [tex]\(h\)[/tex] is [tex]\(h = 0\)[/tex].
1. Start with the given equation:
[tex]\[ (5 - 3)p = 4h + 2p \][/tex]
2. Simplify the left-hand side first:
[tex]\[ 2p = 4h + 2p \][/tex]
3. Next, we need to isolate [tex]\(h\)[/tex]. To do that, we subtract [tex]\(2p\)[/tex] from both sides of the equation:
[tex]\[ 2p - 2p = 4h + 2p - 2p \][/tex]
4. This simplifies to:
[tex]\[ 0 = 4h \][/tex]
5. Now, divide both sides by 4 to solve for [tex]\(h\)[/tex]:
[tex]\[ \frac{0}{4} = \frac{4h}{4} \][/tex]
6. Simplifying this gives:
[tex]\[ 0 = h \][/tex]
So, the solution for [tex]\(h\)[/tex] is:
[tex]\[ h = 0 \][/tex]
This shows that [tex]\(h\)[/tex] must be zero to satisfy the original equation. Additionally, the simplified form of the initial equation:
If we write the equation in a standard linear form related to [tex]\(h\)[/tex]:
[tex]\[0 = -4h\][/tex]
Here, the expression simplifies to:
[tex]\[ -4h \][/tex]
Therefore, the complete solution shows that:
The simplified version of the equation is [tex]\(-4h = 0\)[/tex], and the solution for [tex]\(h\)[/tex] is [tex]\(h = 0\)[/tex].
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Your questions find answers at IDNLearn.com. Thanks for visiting, and come back for more accurate and reliable solutions.